The Role of TNF-α and Total IgE in Pathogenicity of Iraqi Fuel Stations Workers with Allergic Rhinitis - Ahmed, Mays Q.; Hussein, Talib A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Allergic Rhinitis (AR) is a chronic immune system inflammation that occurs when the body overreacts to antigens in the environment (triggers) and produces a variety of symptoms in the nasal mucosa and paranasal sinuses due to the release of many interleukins and cytokines.We investigated the influence of the allergen on serum levels of TNF-α and Total IgE in patients with AR and their function in initiating allergic rhinitis in Iraqi petrol station workers in Baghdad. One hundred individuals with allergic rhinitis and thirty healthy workers between the ages of 20 and 59 were examined. For immunological testing, sandwich ELISA was used to evaluate serum levels of TNF-α and Total IgE. A complete blood cell count (CBC) was used for hematological testing. Findings showed a positive connection between TNF-α and Total IgE, with a correlation of (r=0.32). The TNF-α binary logistic regression analysis (BLR) was conducted to be highly significant (B = 0.02, OR = 1.02, p =0.065), viewing that an increase of one unit in TNF-α increases the odds of belonging to the AR group. TNF-α had the highest area under the curve (AUC) compared to other markers, with a value of (AUC = 0.995), indicating that it is an excellent predictor and strong marker for AR, with a sensitivity and specificity of 94% and 100%, respectively. After our research, we reached the significance of the study from the clarity of the role of tumor necrosis factor-alpha in the disease and its development and the coincidence of its increase with immunoglobulin E and considering. It is also a diagnostic marker of the disease.